Socio-Religious Conflicts in the East Adonara Community of East Nusa Tenggara - Mukin, Taufiq Kurahman Rasyid; Thohir, Ajid; Marjani, Gustiana Isya; Gumilar, Setia (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
On Adonara Island, customary land conflicts began with a rival war, or war between citizens, which occurred due to differences in customary rights over land. There was a conflict between the residents of Narasosina Village and the residents of Lewobunga Village. In this case, the residents of Lewonara Village refused the inauguration of a settlement location for the residents of Lewobunga Village on customary land that was considered to belong to Narasaosina Village. So, the war between the residents of Narasaosina Village and the residents of Lewobunga Village because the request letter to empty the flower casserole was not heeded. In the last twenty years, there have been ten villages that have been warned over customary land rights and there has been no serious settlement. The ten villages that were moaning and had not been resolved were: (1). Redontena Village vs Adobala Village, (2). Sandosi Village vs Sandosi Village (a war fought within the village, between tribes that fight over land), (3). Lamahala vs Huruhura(4). Teulu Old Village vs Kewo Keleng Village, (5). Narasosina Village vs Lewo Bunga Village. To resolve the conflict that occurred in Adonara, East Flores Regency, East Nusa Tenggara, efforts would be made to resolve the conflict. Conflict resolution could be done with conflict management, and conflict resolution was a peaceful method that allows both parties to end or significantly reduce the conflict. It might not be too difficult to handle or help handle conflicts that arise from conflicts of interest.